Suicidal ideation and behavior among perinatal women and their association with sleep disturbances, medical conditions, and known risk factors - Arditi-Arbel, Bar; Hamdan, Sami; Winterman, May; Gvion, Yari (Frontiers in Psychiatry, 2023)
Objective Suicide is considered one of the leading causes of maternal mortality, especially among women with postpartum depression. In the current systematic review, we conducted a qualitative data synthesis of recent studies exploring novel risk factors including sleep disturbances and medical conditions, alongside known and significant risk factors for perinatal suicidality. Evidence acquisition We conducted a systematic search of the literature according to PRISMA guidelines on PubMed, PsycNET, and Scopus databases. Search terms were “pregnancy” “OR” “postpartum” “OR” “peripartum” “OR” “perinatal” “OR” “postnatal” combined with the Boolean “AND” operator with “suicide” “OR” “suicidality” “OR” “suicidal ideation” “OR” “suicidal behavior.” Evidence synthesis The initial search yielded 1,458 records, of which 51 research reports that met inclusion criteria were analyzed. These 51 studies sampled a total of 45,942 participants. Clinically, sleep disturbance, psychopathology, and social support have been identified as dominant risk factors for suicidal behavior among pregnant and postpartum women, as well as medical conditions and aversive life events. Conclusion Monitoring sleep disturbance, depression, and perceived social support is critical given that they are significant risk factors for suicide among perinatal women. Early identification of perinatal women who may be at risk of suicide, although not depressed, is crucial. Limitations The use of tools designed to identify depression to identify suicidal risk, fail to identify women who are at risk but who do not suffer from depression. Other methodological limitations are the lack of longitudinal studies and the complexity of examining suicidal behavior in sample studies.